Preservasi Naskah Kuno di Museum Negeri Provinsi Lampung - Arfinda Ika Choirunisa; Ahmad Basyori; Rahmat Iqbal (Jurnal Pustaka Ilmiah, 2026)
Ancient manuscripts are cultural heritage that has high historical value and is prone to damage, so it requires planned and sustainable preservation efforts. The Lampung Provincial State Museum as a preservation institution stores 47 ancient manuscripts with a variety of organic writing media that require physical and informational preservation. This study aims to examine the implementation of preventive preservation of all ancient manuscripts in the museum and identify the obstacles faced. This study uses a qualitative method with a case study approach through observation, interviews, and documentation. The results of the study show that preventive preservation efforts are carried out through housekeeping nature disaster preparedness plan activities, transfer of information and cooperative action or the use of technology on a large scale. These efforts include regular cleaning of the environment, temperature and lighting regulation, storage of collections in special cabinets, use of acid-free boxes and silica gel to protect manuscripts. Of the 47 manuscripts owned, as many as 29 manuscripts have been transmediated into digital format and can be accessed by the public through the Opus Lampung page. However, preservation activities have not run optimally due to limited digitization facilities and infrastructure, the lack of human resources in the field of preservation, and the characteristics of manuscripts that are very vulnerable to changes in environmental conditions.